Isolamento e caracterização de cepas termotolerantes de Saccharomyces cerevisiae e análise da expressão de genes possivelmente envolvidos com a termotolerância - Souza, Jonas Paulino de (Universidade Federal de São Carlos, 2018)
Brazil is the world’s second largest producer of ethanol, which is produced, in our country, from the fermentation of sugarcane sucrose by Saccharomyces cerevisiae yeast. Despite having a high capacity for ethanol production, the industrial yeasts act in a narrow band of temperature between 30 and 35ºC. In order to maintain this band of temperature, chillers are used, which results in cost increase and water consumption. Besides the temperature, other stress factors, such as high sugar and ethanol concentrations and contamination by microorganisms, also affect the yields of production. In this sense, the present research aimed at isolating and characterizing thermotolerant S. cerevisiae yeast strains from the industrial fermentative process. In addition, the expression of the genes OLE-1, YHR087W and HSP26, which are correlated in literature to different stress factors, was evaluated in these strains. A total of 157 yeasts was analyzed for growth capacity at 40ºC. Eight S. cerevisiae strains, which were identified through the ITS 18S region, were able to grow in this condition. Among the eight strains, four showed excellent glucose consumption at 30 and 40ºC. After 27 fermentative cycles at 40ºC, the four strains showed a preference for growth at this temperature and indicated to be possibly thermotolerant. Previous analyses showed that these strains have a higher capacity for cellular growth, high ethanol concentration and resistance to osmotic stress and acid treatment. Fermentative analyses evidenced that thermotolerant yeasts produced similar quantities of ethanol at 30 and 40ºC. The expression of the genes HSP26 and YHR087W was positively regulated during the fermentation at high temperatures, while the gene OLE-1 reduced the expression at the same condition. The application of thermotolerant yeast strains in fermentations at high temperatures can contribute to increase ethanol production, which is an important strategy to optimize the production of ethanol in Brazil. In addition, the identification of S. cerevisiae genes that were differently expressed under high temperature conditions can contribute to a better understanding of molecular mechanisms that lead to the activation of metabolic pathways responsible for thermotolerance.
Isolation and characterization of thermotolerant Saccharomyces cerevisiae strains and analysis of the expression of genes possibly involved with thermotolerance
Keywords: Etanol; Fermentação; Termotolerância; Saccharomyces cerevisiae; Ethanol; Fermentation; Thermotolerance; Saccharomyces cerevisiae; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR